THE EFFECT OF ENTREPRENEURIAL KNOWLEDGE AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP MEDIATED BY SELF-EFFICACY - Anis Fitrianingsih; Henry Eryanto; Nadya Fadillah Fidhyallah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This research was conducted to determine the effect of Entrepreneurship Knowledge and Family Environment on Interest in Entrepreneurship with Self-Efficacy as an intervening variable in students of SMKN 50 Jakarta. The research method used is a quantitative research method with a descriptive approach. The population used in this study were class XII students at SMKN 50 Jakarta from all majors, namely AKL, BDP, OTKP, and MM consisting of 213 students and students with a sample of 131 students referring to the Isaac and Michael tables. The research model uses a path analysis model and the data analysis technique used is SEM (Structural Equation Modeling) using the SmartPLS version 3 application. From the results of the study, it can be seen that there is a positive and significant influence between the variables of entrepreneurial knowledge on self-mediated entrepreneurial interest. -efficacy, there is a positive and significant influence between family environment variables on interest in entrepreneurship which is mediated by self-efficacy